Assessing the Impact of Visits to the Learning Resource Center and the Multiliteracy Center - Paul Peterson:::::: (2023)
This report provides an assessment the most recent five (5) years of the academic tutoring centers on campus, the Learning Resource Center and the Writing & Multiliteracy Center. The assessment is comprehensive in nature, but the analyses are limited to stateside students, the tutoring centers themselves, and Fall terms. Selecting these parameters was helpful for the scope of the analyses and I believe in line with normative and best practices for these types of assessments. These parameters are also based on the historical and the most recent data that we have available now. Please see end notes for additional methodological considerations.